A COMPREHENSIVE REVIEW ON SUPERSATURABLE SELF-NANOEMULSIFYING DRUG DELIVERY SYSTEM - REDDY, MUTHADI RADHIKA; GUBBIYAPPA, KUMAR SHIVA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Lipid-based drug delivery systems are extensively reported in the literature for enhancing drug solubility, permeability, and bioavailability. Self-nanoemulsifying drug delivery systems (SNEDDS) are a superior strategy for enhancing solubility and bioavailability of poorly water-soluble compounds and the most prevailing and commercially viable oil-based approach for drugs that exhibit low dissolution rate and inadequate absorption. However, these formulations have few limitations that include in vivo drug precipitation, inferior in vitro in vivo correlation owing to unavailability of in vitro tests, handling issues of liquid formulation, and physicochemical instability of drugs. These limitations are overcome by potential systems such as supersaturable SNEDDS (S-SNEDDS) which are prepared by addition of precipitation inhibitors into formulated SNEDDS to maintain drug supersaturation post dispersion in gastrointestinal tract. These systems improve drug bioavailability and reduce the inconsistency of exposure. In addition, these formulations also help to overcome the drawbacks of liquid and capsule dosage forms. The S-SNEDDS provides an effective approach for improving the dissolution and bioavailability of anti-cancer agents. In this article, an attempt was made to present an overview of SNEDDS, S-SNEDDS, their mechanism, formulation excipients, recent advancements, advantages, and disadvantages of SNEDDS formulations. The article also focuses on reviewing the application of S-SNEDDS in enhancing the solubility and bioavailability of anti-cancer drugs in cancer therapy.